Implementation of an Effective Daily Activity Schedule to Improve Student Time Management - Lambok Manurung; Amril; Irma Herliza Rizki; Nur Yasmin (Outline Publisher, 2024)
Optimizing time management is an important aspect in the lives of students in Islamic boarding schools, where good time management can improve the quality of learning, worship, and student welfare. This service aims to improve students' time management through the implementation of an effective daily activity schedule. Through initial observations, it was found that many students had difficulty in managing their time in a structured manner. Therefore, this activity involved compiling a daily activity schedule that included time for studying, worship, rest, and social activities. The implementation of the schedule was carried out for one month and was evaluated through interviews and observations. The results showed that students felt more disciplined, organized, and had more optimal time to study and rest. However, several improvements related to the duration of rest and flexibility of study time still need to be made. Overall, the implementation of a daily activity schedule has proven effective in helping students optimize their time management in Islamic boarding schools.